Improving the Production Quality and Competitiveness of Housewife Weaving through the Acquisition of Intellectual Property Rights in the Innovation of Sekir Handloom and Weaving Handloom in Balla Tumuka Village - Kartika, Eka Dewi; Erwin, Erwin; Novitasari, Ika; Iba, Wa; Riani, Irdam (Abdi Masyarakat, 2023)
Housewives weavers in Balla tumuka Village, as the main partners in this activity, carry out weaving activities in a traditional way using godokan tools. This has implications for the low quality of woven fabrics and a long time to make woven products. In addition, Balla Tumuka village is included in the category of very underdeveloped villages, so it also has implications for marketing methods that are not effective and efficient. The second partner in this activity is Bumdes Balla tumuka with the problem of Bumdes activities as a grocery store, so has implications for the lack of development of bumdes. Then, through the nation's vocabulary programme implemented according to the needs of the weaving group of housewives and bumdes, to increase the competitiveness of their respective products through intellectual property, namely trademarks on products owned by Bumdes and Weavers, and Copyright by the Weaving Group on Motifs.